Rasch Model: Analisis Soal Biologi pada Kurikulum Indonesia Merdeka - Kalika Azra Zainina; Mia Zubaidah Mufiqoh; Nani Aprilia; Bekti Isnaeni (Postgraduate, University of Mataram, 2024)
The change from the 2013 curriculum to the independent curriculum has an impact on assessment, one of which is summative assessment. Summative assessment uses multiple choice questions, but the quality of the questions has not been analysed. This descriptive quantitative research aims to determine the quality of summative assessment questions in Biology class X odd semester which includes validity, reliability, difficulty level, and differentiating power. Research subjects were all grade X students. Object of research includes question grids, answer keys, questions, and student answer sheets. The sampling technique used was purposive sampling, and Kurmer Yogyakarta Pilot Project High School was selected. Data were collected through documentation. The instruments in this study were question grids, answer keys, questions, and student answer sheets. The data analysis technique used was quantitative descriptive analysis using Winsteps software version 3.73. The results of quantitative analysis of summative assessment questions in four schools showed valid results. The questions proved to be reliable, with difficulty levels in the easy and difficult categories. The questions had good and sufficient differentiating power. Distractor effectiveness was rated as poor, very good, good, and fair. Qualitative analysis of the 4 schools showed good results, but some improvements were still needed.